2013
DOI: 10.1007/s13139-013-0245-1
|View full text |Cite
|
Sign up to set email alerts
|

Can Initial 18F-FDG PET-CT Imaging Give Information on Metastasis in Patients with Primary Renal Cell Carcinoma?

Abstract: PurposeThe aim of this study was to investigate the relationship between the maximum standardized uptake values (SUVmax) of primary renal cancers with and without metastatic lesions, if any. We also studied the relationship between the size of primary renal cancers and their SUVmax, and tried to find a clinical value of 18F-FDG PET-CT for the initial evaluation of renal cell carcinoma (RCC).MethodsThe cases of 23 patients, 16 men and 7 women, who underwent PET-CT examination before operation were retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…The highest FDG accumulation was seen in the tumor of the highest grade, and the highest mortality was found for tumors exceeding SUV max of 10. Lee et al investigated the relationship between the SUV max of primary RCC with and without metastatic lesions in 23 patients ( 20 ). The median SUV max of primary RCC of the 16 patients without metastasis was 2.6 (range of 1.1–5.6) while that of the patients with metastasis was 5.0 (range of 2.9–7.6).…”
Section: Predictive Role Of Fdg Pet/ct In Prognosismentioning
confidence: 99%
“…The highest FDG accumulation was seen in the tumor of the highest grade, and the highest mortality was found for tumors exceeding SUV max of 10. Lee et al investigated the relationship between the SUV max of primary RCC with and without metastatic lesions in 23 patients ( 20 ). The median SUV max of primary RCC of the 16 patients without metastasis was 2.6 (range of 1.1–5.6) while that of the patients with metastasis was 5.0 (range of 2.9–7.6).…”
Section: Predictive Role Of Fdg Pet/ct In Prognosismentioning
confidence: 99%
“…found that the median SUVmax of the primary RCC of 16 patients without metastasis was 2.6 (range of 1.1–5.6) while that of the patients with metastasis was 5.0 (range of 2.9–7.6). [ 30 ] Thus FDG PET/CT may help in predicting the extrarenal disease, as a primary RCC with a high SUVmax has a higher likelihood of having occult metastasis. Besides the SUV values, metabolic parameters such as the metabolic tumor volume and the total lesion glycolysis calculated with PET imaging also have a prognostic significance as suggested by Hwang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a retrospective study looked at FDG PET in 23 patients, which was acquired before nephrectomy. The study concluded that a high standardized uptake value max at primary RCC reflected a higher likelihood of metastatic disease (5.3 Ϯ 1.7 in metastatic disease vs. 2.9 Ϯ 1.0 in nonmetastatic disease) [65].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%